Polyurethane resin aqueous dispersion for binder used in lithium secondary battery, binder for electrode, and lithium secondary battery
By using a specific composition of polyurethane resin aqueous dispersion in lithium secondary batteries, the problem of structural instability of existing adhesives during charging and discharging is solved, and the ionic conductivity and discharge retention rate are achieved, and the bonding of the electrode and battery performance are improved.
Patent Information
- Application Number
- CN202180044857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-21
- Filing Date
- 2021-10-06
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2041-10-06
AI Technical Summary
The existing lithium secondary battery binder cannot maintain the electrode structure during repeated charging and discharging, resulting in poor ionic conductivity and discharge retention.
Using a polyurethane resin aqueous dispersion, the polyurethane resin aqueous dispersion formed by reacting a polyisocyanate compound, a compound with an active hydrogen group and a chain extender in water, and a combination of polyolefins and polycarbonate within a specific crosslinking density range is improved to improve the adhesion and ionic conductivity.
The ionic conductivity, adhesion and discharge retention rate of lithium secondary batteries are significantly improved, and the structural stability of the electrode is enhanced.
Smart Images

Figure GDA0004013037090000061 
Figure GDA0004013037090000221
Abstract
Description
Technical Field
[0001] The present invention relates to a polyurethane resin aqueous dispersion for a binder used in a lithium secondary battery, a binder for an electrode, and a lithium secondary battery. Background Art
[0002] Conventionally, as a power source for portable terminals such as notebook personal computers, mobile phones, and PDAs (Personal Digital Assistant), a secondary battery is known (for example, Patent Document 1).
[0003] In Patent Documents 1, 2, and 3, styrene-butadiene rubber (SBR) is used as a binder used in an electrode of a secondary battery.
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Patent Laid-Open No. 5-21068
[0007] Patent Document 2: Japanese Patent Laid-Open No. 11-7948
[0008] Patent Document 3: Japanese Patent Laid-Open No. 2001-210318 Summary of the Invention
[0009] Technical Problem to be Solved by the Invention
[0010] However, the binders described in Patent Documents 1, 2, and 3 are insulating materials, and the structure and conduction path of the electrode cannot be maintained with repeated charge and discharge. Therefore, there is room for improvement in ionic conductivity and discharge retention rate. Accordingly, it is desired to develop a technology related to a binder having excellent ionic conductivity, adhesiveness, and discharge retention rate.
[0011] Technical Means for Solving the Problem
[0012] The present invention has been completed to solve the above problems and can be achieved in the following manner.
[0013] (1) According to one aspect of the present invention, there is provided a polyurethane resin aqueous dispersion for a binder used in a lithium secondary battery. The polyurethane resin aqueous dispersion for a binder is characterized in that it is a polyurethane resin aqueous dispersion obtained by dispersing a polyurethane resin, which is obtained by reacting a polyisocyanate compound (a), a compound (b) having two or more active hydrogen groups, a compound (c) having a hydrophilic group and one or more active hydrogen groups, and a chain extender (d), in water. The compound (b) contains: a polyolefin (b1) having two or more active hydrogen groups; and a polycarbonate (b2) having two or more active hydrogen groups and having 6 or less consecutive carbon atoms. The crosslinking density per 1000 molecular weight of the resin solid content contained in the polyurethane resin aqueous dispersion is 0.02 mol / kg or more and 0.28 mol / kg or less.
[0014] According to this aspect, it is possible to provide a binder for a lithium secondary battery having excellent ionic conductivity, adhesiveness, and discharge retention rate.
[0015] (2) In the polyurethane resin aqueous dispersion for a binder according to the above aspect, it may also be that, with respect to 100 parts by mass of the total blending amount of the polyolefin (b1) and the polycarbonate (b2), the polycarbonate (b2) is 5 parts by mass or more and 95 parts by mass or less.
[0016] According to this aspect, the adhesiveness can be improved.
[0017] (3) In the polyurethane resin aqueous dispersion for a binder according to the above aspect, it may also be that, with respect to 100 parts by mass of the total blending amount of the polyolefin (b1) and the polycarbonate (b2), the polycarbonate (b2) is 40 parts by mass or more and 80 parts by mass or less.
[0018] According to this aspect, the adhesiveness can be improved.
[0019] (4) In the polyurethane resin aqueous dispersion for a binder according to the above aspect, it may also be that the polyisocyanate compound (a) contains at least one of an aromatic polyisocyanate and an alicyclic polyisocyanate.
[0020] According to this aspect, it is possible to provide a binder for a lithium secondary battery having more excellent adhesiveness and discharge retention rate.
[0021] (5) In the polyurethane resin aqueous dispersion for a binder according to the above aspect, it may also be that the polyolefin (b1) may contain a polyolefin having two or more hydroxyl groups.
[0022] According to this aspect, it is possible to provide a binder for a lithium secondary battery having more excellent adhesiveness and discharge retention rate.
[0023] (6) In the polyurethane resin aqueous dispersion for a binder in the above-described manner, the polycarbonate (b2) may also contain a polycarbonate having two or more hydroxyl groups.
[0024] According to this manner, a binder for a lithium secondary battery with more excellent ionic conductivity and discharge retention rate can be provided.
[0025] (7) In the polyurethane resin aqueous dispersion for a binder in the above-described manner, the compound (c) may also contain a compound having an active hydrogen group and a carboxyl group.
[0026] According to this manner, a binder for a lithium secondary battery with excellent ionic conductivity, adhesiveness, and discharge retention rate can be provided.
[0027] (8) In the polyurethane resin aqueous dispersion for a binder in the above-described manner, the chain extender (d) may also contain a triamine.
[0028] According to this manner, the electrolyte resistance can be improved.
[0029] (9) In the polyurethane resin aqueous dispersion for a binder in the above-described manner, the chain extender (d) may also be 0.2 parts by mass or more and 1 part by mass or less with respect to 100 parts by mass of the total blending amount of the polyisocyanate compound (a), the compound (b), the compound (c), and the chain extender (d).
[0030] According to this manner, a binder for a lithium secondary battery with excellent ionic conductivity, adhesiveness, and discharge retention rate can be provided.
[0031] (10) According to another aspect of the present invention, there is provided a binder for an electrode, which contains the polyurethane resin aqueous dispersion for a binder in the above-described manner.
[0032] (11) According to another aspect of the present invention, there is provided a lithium secondary battery, which includes an electrode using the binder for an electrode in the above-described manner. Detailed Embodiments
[0033] Hereinafter, preferred embodiments of the present invention will be described.
[0034] <Polyurethane Resin Aqueous Dispersion>
[0035] The polyurethane resin aqueous dispersion for a binder used in a lithium secondary battery according to an embodiment of the present invention (hereinafter, also simply referred to as "polyurethane resin aqueous dispersion") is an aqueous dispersion of a polyurethane resin obtained by reacting a polyisocyanate compound (a), a compound (b) having two or more active hydrogen groups, a compound (c) having a hydrophilic group and one or more active hydrogen groups, and a chain extender (d) in water. The compound (b) contains: a polyolefin (b1) having two or more active hydrogen groups; and a polycarbonate (b2) having two or more active hydrogen groups and having 6 or less consecutive carbon atoms. The crosslinking density per 1000 molecular weights of the resin solid content contained in the polyurethane resin aqueous dispersion is 0.02 mol / kg or more and 0.28 mol / kg or less. In the present specification, the "active hydrogen group" is a functional group that reacts with an isocyanate group, and examples thereof include a hydroxyl group, a primary amino group, a secondary amino group, and a thiol group. As the active hydrogen group, a hydroxyl group is preferred.
[0036] By using the polyurethane resin aqueous dispersion of this form as a binder for a lithium secondary battery, a binder excellent in ionic conductivity, adhesiveness, and discharge retention rate can be obtained. The mechanism is not yet clear, but the following speculative mechanism can be considered. That is, as a compound having two or more active hydrogen groups, there is a problem that the ionic conductivity is not excellent if only a polyolefin is used, but by using a polycarbonate having two or more active hydrogen groups and having 6 or less consecutive carbon atoms in combination, the ionic conductivity, adhesiveness, and discharge retention rate are excellent. In addition, it can be considered that by making the crosslinking density per 1000 molecular weights of the resin solid content contained in the polyurethane resin aqueous dispersion within the above range, a certain strength can be maintained even in a state where the polycarbonate component is swollen in the electrolyte, and thus the discharge retention rate is excellent.
[0037] The crosslinking density per 1000 molecular weights of the resin solid content contained in the polyurethane resin aqueous dispersion is more preferably 0.03 mol / kg or more, further preferably 0.04 mol / kg or more, and particularly preferably 0.05 mol / kg or more. In addition, it is preferably 0.25 mol / kg or less, more preferably 0.20 mol / kg or less, and particularly preferably 0.10 mol / kg or less.
[0038] It should be noted that the crosslinking density in the present specification can be calculated by the following method. That is, it can be calculated by the following formula for a polyisocyanate compound (a) having a mass of W A1 g, a molecular weight MW A1 and a functional group number F A1 , a polyisocyanate compound (a) having a mass of W A2 g, a molecular weight MW A2 and a functional group number F A2The polyisocyanate compound (a), with a mass of W Aj g, a molecular weight MW Aj and a functional group number F Aj The polyisocyanate compound (a) (where j is an integer of 1 or more), with a mass of W B1 g, a molecular weight MW B1 and a functional group number F B1 And a compound (b) having two or more active hydrogen groups, with a mass of W B2 g, a molecular weight MW B2 and a functional group number F B2 And a compound (b) having two or more active hydrogen groups, with a mass of W Bk g, a molecular weight MW Bk and a functional group number F Bk And a compound (b) having two or more active hydrogen groups (where k is an integer of 1 or more), with a mass of W C1 g, a molecular weight MW C1 and a functional group number F C1 And a compound (c) having a hydrophilic group and one or more active hydrogen groups, with a mass of W Cm g, a molecular weight MW Cm and a functional group number F Cm And a compound (c) having a hydrophilic group and one or more active hydrogen groups (where m is an integer of 1 or more), with a mass of W D1 g, a molecular weight MW D1 and a functional group number F D1 And a chain extender (d) and a mass of W Dn g, a molecular weight MW Dn and a functional group number F Dn The crosslinking density per 1000 molecular weights of the resin solid content contained in the polyurethane resin aqueous dispersion obtained by reacting the chain extender (d) (where n is an integer of 1 or more).
[0039] [Equation 1]
[0040]
[0041] <Polyisocyanate compound (a)>
[0042] The polyisocyanate compound is not particularly limited, and for example, organic polyisocyanates can be cited. The organic polyisocyanate is not particularly limited, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, araliphatic polyisocyanates, etc. Examples of the aliphatic polyisocyanate include tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, 3-methylpentane-1,5-diisocyanate, etc. Examples of the alicyclic polyisocyanate include isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane, etc. Examples of the aromatic polyisocyanate include toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-dibenzyl diisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, hydrogenated diphenylmethane diisocyanate, etc. Examples of the araliphatic polyisocyanate include dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, α,α,α,α-tetramethylxylylene diisocyanate, etc. In addition, as the polyisocyanate compound, modified products such as dimers or trimers of these organic polyisocyanates and biuretized isocyanates can be cited. The polyisocyanate compound can be used alone or in combination of two or more.
[0043] As the polyisocyanate compound, from the viewpoints of excellent electrolyte resistance and adhesiveness, aromatic polyisocyanates and alicyclic polyisocyanates are preferred, and alicyclic polyisocyanates are more preferred. Specifically, as the polyisocyanate compound, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and hydrogenated diphenylmethane diisocyanate are preferred, and hydrogenated diphenylmethane diisocyanate is more preferred.
[0044] <Compound (b) having two or more active hydrogen groups>
[0045] The compound (b) having two or more active hydrogen groups contains: a polyolefin (b1) having two or more active hydrogen groups; and a polycarbonate (b2) having two or more active hydrogen groups and having 6 or less carbon atoms in a continuous manner.
[0046] (Polyolefin (b1) having two or more active hydrogen groups)
[0047] The polyolefin (b1) having two or more active hydrogen groups is a polyolefin containing two or more active hydrogen groups selected from the group consisting of a hydroxyl group, a primary amino group, a secondary amino group, and a thiol group. The two or more active hydrogen groups contained in the polyolefin (b1) may be the same functional group or different functional groups. In the present specification, "polyolefin" means a polymer of an aliphatic hydrocarbon compound having a double bond such as ethylene, propylene, butene, butadiene, and isoprene. As the polyolefin (b1) having two or more active hydrogen groups, from the viewpoint of excellent electrolyte resistance and adhesiveness, a polyolefin containing one or more hydroxyl groups is preferred, and a polyolefin containing two or more hydroxyl groups is more preferred.
[0048] The polyolefin (b1) containing two or more hydroxyl groups is not particularly limited, and examples thereof include polybutadiene polyol, polyisoprene polyol, and polychloroprene polyol. As the polyolefin (b1) containing two or more hydroxyl groups, for example, a polyolefin obtained by hydrogenating the above polyolefin, or a polyolefin obtained by copolymerizing other olefin compounds can be cited.
[0049] As the polyolefin (b1) having two or more active hydrogen groups, polybutadiene polyol and polyisoprene polyol are preferred, and polybutadiene polyol is more preferred.
[0050] (Polycarbonate (b2) having two or more active hydrogen groups and a continuous carbon atom number of 6 or less)
[0051] In the present embodiment, a polycarbonate (b2) having two or more active hydrogen groups and a continuous carbon atom number of 6 or less is used. By using a polycarbonate having a continuous carbon atom number of 6 or less, when the polyurethane resin aqueous dispersion of the present embodiment is used as a binder, the affinity with the electrolyte is excellent, and thus the ionic conductivity is excellent.
[0052] The polycarbonate (b2) has two or more active hydrogen groups selected from the group consisting of a hydroxyl group, a primary amino group, a secondary amino group, and a thiol group, and the continuous carbon atom number is 6 or less. The two or more active hydrogen groups contained in the polycarbonate (b2) may be the same functional group or different functional groups. From the viewpoints of excellent electrolyte resistance, ionic conductivity, adhesiveness, and discharge retention rate, the polycarbonate (b2) preferably contains a polycarbonate having one or more hydroxyl groups, and more preferably contains a polycarbonate having two or more hydroxyl groups.
[0053] As the polycarbonate (b2), there is no particular limitation, and for example, polycarbonate polyols commonly used in this technical field can be used. Examples of the polycarbonate polyol include carbonate polyols of 1,6 - hexanediol, carbonate polyols of 1,4 - butanediol and 1,6 - hexanediol, carbonate polyols of 1,5 - pentanediol and 1,6 - hexanediol, carbonate polyols of 3 - methyl - 1,5 - pentanediol and 1,6 - hexanediol, etc. More specifically, examples include PCDL T - 6001, T - 6002, T - 5651, T - 5652, T - 5650J, T - 4671, T - 4672 manufactured by Asahi Kasei Corporation; Kuraray Polyol C - 590, C - 1050, C - 1050R, C - 1090, C - 2050, C - 2050R, C - 2070, C - 2070R, C - 2090, C - 2090R, C - 3090, C - 3090R, C - 4090, C - 4090R, C - 5090, C - 5090R, C - 1065N, C - 2065N, C - 1015N, C - 2015N manufactured by Kuraray Co., Ltd.; ETERNACOLL (registered trademark) UH - 50, UH - 100, UH - 200, UH - 300, UM - 90(3 / 1), UM - 90(1 / 1), UM - 90(1 / 3), UC - 100 manufactured by Ube Industries, Ltd., etc.
[0054] With respect to the total blending amount of the polyolefin (b1) and the polycarbonate (b2), there is no particular limitation on the polycarbonate. From the viewpoint of ionic conductivity, it is preferably 5 parts by mass or more, more preferably 30 parts by mass or more, and further preferably 40 parts by mass or more. In addition, with respect to the total blending amount of the polyolefin (b1) and the polycarbonate (b2), there is no particular limitation on the polycarbonate. From the viewpoint of electrolyte resistance, it is preferably 95 parts by mass or less, more preferably 80 parts by mass or less, and further preferably 60 parts by mass or less.
[0055] <Compound (c) having a hydrophilic group and one or more active hydrogen groups>
[0056] In this specification, as the "hydrophilic group", anionic hydrophilic groups, cationic hydrophilic groups, and non - ionic hydrophilic groups can be cited. Examples of the anionic hydrophilic group include a carboxyl group and its salts, a sulfonic acid group and its salts. Examples of the cationic hydrophilic group include tertiary ammonium salts and quaternary ammonium salts. Examples of the non - ionic hydrophilic group include a group containing ethylene oxide repeating units, a group containing ethylene oxide repeating units and other alkylene oxide repeating units, etc.
[0057] As compounds each having one or more active hydrogen groups and one or more carboxyl groups or their salts, examples include carboxylic acid-containing compounds such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolvaleric acid, dihydroxymaleic acid, 2,6-dihydroxybenzoic acid, 3,4-diaminobenzoic acid, and their derivatives and their salts, and polyester polyols obtained by using them. In addition, amino acids such as alanine, aminobutyric acid, aminohexanoic acid, glycine, glutamic acid, aspartic acid, and histidine can be cited; carboxylic acids such as succinic acid, adipic acid, maleic anhydride, phthalic acid, and trimellitic anhydride can be cited.
[0058] As compounds each having one or more active hydrogen groups and one or more sulfonic acid groups (or their salts), examples include sulfonic acid-containing compounds such as 2-oxoethanesulfonic acid, phenolsulfonic acid, sulfobenzoic acid, sulfosuccinic acid, 5-sulfoisophthalic acid, aminobenzenesulfonic acid, 1,3-phenylenediamine-4,6-disulfonic acid, 2,4-diaminotoluene-5-sulfonic acid, and their derivatives, and polyester polyols, polyamide polyols, polyamide polyester polyols, etc. obtained by copolymerizing them.
[0059] By neutralizing these carboxyl groups or sulfonic acid groups to form salts, the finally obtained polyurethane can be made water-dispersible. As neutralizing agents in this case, for example, non-volatile bases such as sodium hydroxide and potassium hydroxide, or tertiary amines such as trimethylamine, triethylamine, dimethylethanolamine, methyldiethanolamine, and triethanolamine, and volatile bases such as ammonia can be cited. Neutralization can be carried out either before, during, or after the urethane formation reaction.
[0060] Examples of compounds having one or more active hydrogen groups and tertiary ammonium salts include alkanolamines such as methylaminoethanol and methyldiethanolamine. By neutralizing them with organic carboxylic acids such as formic acid and acetic acid or inorganic acids such as hydrochloric acid and sulfuric acid to form salts, the polyurethane can be made water-dispersible. Neutralization can be carried out either before, during, or after the urethane formation reaction. Among them, from the viewpoint of ease of emulsification, a substance obtained by neutralizing methyldiethanolamine with an organic carboxylic acid is preferred.
[0061] Compounds having one or more active hydrogen groups and quaternary ammonium salts are compounds obtained by quaternizing the aforementioned alkanolamines such as methylaminoethanol and methyldiethanolamine with haloalkyls such as chloromethane and bromomethyl, and dialkyl sulfates such as dimethyl sulfate. Among them, from the viewpoint of ease of emulsification, a compound obtained by quaternizing methyldiethanolamine with dimethyl sulfate or the like is preferred.
[0062] The compound having at least one active hydrogen group and at least one nonionic hydrophilic group is not particularly limited, and preferably a compound containing at least 30% by mass or more of ethylene oxide repeating units and having a number average molecular weight of 300 to 20,000. For example, there can be mentioned: polyoxyethylene glycol, poly(ethylene oxide - propylene oxide) copolymer diol, poly(ethylene oxide - butylene oxide) copolymer diol, poly(ethylene oxide - polyalkylene oxide) copolymer diol or its monoalkyl ether and other compounds containing nonionic groups, or polyester polyether polyols obtained by copolymerizing them, etc.
[0063] <Chain extender (d)>
[0064] As the chain extender (d), there is no particular limitation, and for example, diamines, triamines, tetraamines, etc. can be mentioned. As diamines, for example, ethylenediamine, trimethylenediamine, piperazine, isophoronediamine, etc. can be mentioned. As triamines, for example, diethylenetriamine, dipropylenetriamine, etc. can be mentioned. As tetraamines, for example, triethylenetetramine, etc. can be mentioned. In order to improve the electrolyte resistance, as the chain extender (d), triamines are preferred, and diethylenetriamine is more preferred.
[0065] The blending amount of the chain extender (d) is not particularly limited. From the viewpoint of balancing electrolyte resistance and adhesiveness, relative to 100 parts by mass of the polyurethane resin, it is preferably 0.1 part by mass or more and 3 parts by mass or less, and more preferably 0.2 part by mass or more and 1 part by mass or less.
[0066] The solid content of the polyurethane resin in the polyurethane resin aqueous dispersion is not particularly limited. From the viewpoint of operability, relative to 100 parts by mass of the polyurethane resin aqueous dispersion, it is preferably 1 part by mass or more and 60 parts by mass or less, more preferably 3 parts by mass or more and 55 parts by mass or less, and further preferably 4 parts by mass or more and 50 parts by mass or less.
[0067] Furthermore, in the polyurethane resin aqueous dispersion, various commonly used additives can be used as needed. As such additives, there is no particular limitation, and for example, weathering agents, antibacterial agents, antifungal agents, pigments, rust inhibitors, dyes, film-forming aids, inorganic crosslinking agents, organic crosslinking agents, silane coupling agents, anti-blocking agents, viscosity regulators, leveling agents, defoaming agents, dispersion stabilizers, light stabilizers, antioxidants, ultraviolet absorbers, inorganic fillers, organic fillers, plasticizers, lubricants, antistatic agents, etc. can be mentioned. As the organic crosslinking agent, there is no particular limitation, and for example, blocked isocyanate-based crosslinking agents, epoxy-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, melamine-based crosslinking agents, etc. can be mentioned.
[0068] <Method for preparing polyurethane resin aqueous dispersion>
[0069] As a method for manufacturing a polyurethane resin aqueous dispersion, there is no particular limitation, and a known method can be used. As a method for manufacturing a polyurethane resin aqueous dispersion, for example, the following method can be cited. First, a polyisocyanate compound (a), a compound (b), and a compound (c) are reacted under reaction conditions of 30°C to 130°C for about 0.5 hours to 10 hours, and then it is cooled to 5°C to 45°C as needed. By doing so, a urethane prepolymer can be obtained by neutralizing the hydrophilic group or by previously adding a quaternizing agent for quaternization. In addition, as the solvent, any organic solvent such as acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, ethyl acetate, and butyl acetate can be used. Furthermore, a polyurethane resin aqueous dispersion can be manufactured by emulsifying and chain-extending the urethane prepolymer. As the water used in the emulsification, it is preferable to add 100 to 900 parts by mass of water relative to 100 parts by mass of the urethane prepolymer.
[0070] Next, the lithium secondary battery of the present embodiment will be described. The positive electrode and the negative electrode used in the lithium secondary battery of the present embodiment are composed of an electrode active material, a conductive agent, a current collector of the electrode active material, a binder for bonding the electrode active material and the conductive agent to the current collector, and the like.
[0071] The lithium secondary battery of the present embodiment is composed of electrodes manufactured using a binder containing the polyurethane resin aqueous dispersion of the above embodiment. The above binder can be used in both the positive electrode and the negative electrode, or can be used in either the positive electrode or the negative electrode.
[0072] In the lithium secondary battery of the present embodiment, as a binder for the electrode that does not use the above polyurethane resin aqueous dispersion, polyvinylidene fluoride, a polyvinylidene fluoride copolymer resin such as a copolymer of polyvinylidene fluoride and hexafluoropropylene, perfluoromethyl vinyl ether, and tetrafluoroethylene, a fluororesin such as polytetrafluoroethylene and fluororubber, a polymer such as styrene-butadiene rubber, ethylene-butadiene rubber, and styrene-acrylonitrile copolymer can be used, but it is not limited thereto.
[0073] As the positive electrode active material used in the positive electrode of the lithium secondary battery of the present embodiment, there is no particular limitation as long as it can insert and remove lithium ions. As examples, metal oxides such as CuO, Cu2O, MnO2, MoO3, V2O5, CrO3, MoO3, Fe2O3, Ni2O3, and CoO3 can be cited; Li x CoO2, Li x NiO2, Li xComposite oxides of lithium and transition metals such as Mn2O4 and LiFePO4; metal chalcogenides such as TiS2, MoS2, and NbSe3; conductive polymer compounds such as polyacene, polyphenylene, polypyrrole, and polyaniline, etc. Among the above, from the aspects of easy release of lithium ions and high voltage, a composite oxide of one or more selected from transition metals such as cobalt, nickel, and manganese and lithium, which is generally called a high-voltage system, is preferably used. Specific examples of the composite oxide of cobalt, nickel, manganese and lithium include: LiCoO2, LiMnO2, LiMn2O4, LiNiO2, LiNi x Co (1-x) O2, LiMn a Ni b Co c (a + b + c = 1), etc. In addition, substances obtained by doping a small amount of elements such as fluorine, boron, aluminum, chromium, zirconium, molybdenum, and iron in these lithium composite oxides, or substances obtained by surface-treating the particle surfaces of lithium composite oxides with carbon, MgO, Al2O3, SiO2, etc. can also be used. Two or more of the above positive electrode active materials can also be used in combination.
[0074] As the negative electrode active material used in the negative electrode of the present embodiment, as long as it can insert / remove metallic lithium or lithium ions, a known active material can be used without particular limitation. For example, carbon materials such as natural graphite, artificial graphite, hard-to-graphitize carbon, and easy-to-graphitize carbon can be used. In addition, metal materials such as metallic lithium, alloys, and tin compounds, lithium transition metal nitrides, crystalline metal oxides, amorphous metal oxides, silicon compounds, conductive polymers, etc. can also be used. Specific examples include Li4Ti5O 12 , NiSi5C6, etc.
[0075] A conductive agent is used in the positive electrode and negative electrode of the lithium secondary battery of the present embodiment. As the conductive agent, as long as it is an electron-conductive material that does not have an adverse effect on the battery performance, it can be used without particular limitation. Usually, carbon blacks such as acetylene black and Ketjen black are used, but natural graphite (scaly graphite, flaky graphite, earthy graphite, etc.), artificial graphite, carbon whiskers, carbon fibers, or powders of metals (copper, nickel, aluminum, silver, gold, etc.), metal fibers, conductive ceramic materials, etc. can also be used. They can also be used in the form of a mixture of two or more conductive materials. The addition amount is preferably 0.1 to 30% by mass, particularly preferably 0.2 to 20% by mass, based on the amount of the active material.
[0076] As the current collector of the electrode active material of the lithium secondary battery of the present embodiment, any electronic conductor that does not have an adverse effect on the formed battery can be arbitrarily used. For example, as the current collector for the positive electrode, in addition to aluminum, titanium, stainless steel, nickel, fired carbon, conductive polymers, conductive glass, etc., for the purpose of improving adhesion, conductivity, and oxidation resistance, current collectors obtained by treating the surfaces of aluminum, copper, etc. with carbon, nickel, titanium, silver, etc. can be used. In addition, as the current collector for the negative electrode, in addition to copper, stainless steel, nickel, aluminum, titanium, fired carbon, conductive polymers, conductive glass, Al-Cd alloy, etc., for the purpose of improving adhesion, conductivity, and oxidation resistance, current collectors obtained by treating the surfaces of copper, etc. with carbon, nickel, titanium, silver, etc. can be used. These current collector materials can also be subjected to surface oxidation treatment. In addition, regarding its shape, in addition to foil-like shapes, shaped bodies such as film-like, sheet-like, mesh-like, punched or expanded objects, slats, porous bodies, foams, etc. can also be used. The thickness is not particularly limited, and a thickness of 1 to 100 μm is usually used.
[0077] The electrode of the lithium secondary battery of the present embodiment can be manufactured by mixing an electrode active material, a conductive agent, and a binder that binds the electrode active material and the conductive agent to the current collector to prepare a paste-like electrode material, and coating it on an aluminum foil, copper foil, etc. that serves as the current collector to volatilize the dispersion medium.
[0078] In the electrode material of the present embodiment, as a viscosity modifier for making a paste, thickeners such as water-soluble polymers can be used. Specifically, one or more selected from cellulose-based materials such as carboxymethyl cellulose salts, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose; polycarboxylic acid-based compounds such as polyacrylic acid, sodium polyacrylate; compounds having a vinylpyrrolidone structure such as polyvinylpyrrolidone; polyacrylamide, polyethylene oxide, polyvinyl alcohol, sodium alginate, xanthan gum, carrageenan, guar gum, agar, starch, etc. can be used, and among them, carboxymethyl cellulose salts are preferred.
[0079] The method, order, etc. of mixing the above electrode materials are not particularly limited. For example, the active material and the conductive agent can be pre-mixed and used. In the mixing in this case, ball mills such as mortars, grinders, planetary ball mills or rocking ball mills, mechanical fusion, etc. can be used.
[0080] The separator used in the lithium secondary battery of the present embodiment can be the separator commonly used in ordinary lithium secondary batteries without particular limitation. Examples thereof include porous resins, ceramics, non-woven fabrics, etc. composed of polyethylene, polypropylene, polyolefins, polytetrafluoroethylene, etc.
[0081] In the lithium secondary battery of the present embodiment, the electrolytic solution used may be an electrolytic solution commonly used in a lithium secondary battery, and general electrolytic solutions such as an organic electrolytic solution and an ionic liquid can be used.
[0082] Examples of the electrolyte salt used in the lithium secondary battery of the present embodiment include LiPF6, LiBF4, LiClO4, LiAsF6, LiCl, LiBr, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, LiI, LiAlCl4, NaClO4, NaBF4, NaI, etc. Inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAsF6, etc., and organic lithium salts represented by LiN(SO2C x F 2x+1 )(SO2C y F 2y+1 ) are particularly preferred. Here, x and y represent integers of 0 or 1 to 4, and in addition, x + y is 2 to 8. Examples of the organic lithium salt include LiN(SO2F)2, LiN(SO2CF3)(SO2C2F5), LiN(SO2CF3)(SO2C3F7), LiN(SO2CF3)(SO2C4F9), LiN(SO2C2F5)2, LiN(SO2C2F5)(SO2C3F7), LiN(SO2C2F5)(SO2C4F9), etc. Among them, if LiPF6, LiBF4, LiN(CF3SO2)2, LiN(SO2F)2, LiN(SO2C2F5)2, etc. are used as the electrolyte, the electrical characteristics are excellent, and thus they are preferred. The above electrolyte salts may be used singly or in combination of two or more. Such lithium salts are usually contained in the electrolytic solution at a concentration of 0.1 to 2.0 mol / L, preferably at a concentration of 0.3 to 1.5 mol / L.
[0083] As the organic solvent for dissolving the electrolyte salt of the lithium secondary battery of the present embodiment, there is no particular limitation as long as it is an organic solvent used in a non-aqueous electrolyte of a general lithium secondary battery. For example, carbonate compounds, lactone compounds, ether compounds, sulfolane compounds, dioxolane compounds, ketone compounds, nitrile compounds, halogenated hydrocarbon compounds, etc. can be cited. Specifically, carbonate esters such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, ethylene glycol dimethyl carbonate, propylene glycol dimethyl carbonate, ethylene glycol diethyl carbonate, vinylene carbonate, etc., lactones such as γ-butyrolactone, ethers such as dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,4-dioxane, etc., sulfolanes such as sulfolane, 3-methylsulfolane, etc., dioxolanes such as 1,3-dioxolane, ketones such as 4-methyl-2-pentanone, nitriles such as acetonitrile, propionitrile, valeronitrile, benzonitrile, etc., halogenated hydrocarbons such as 1,2-dichloroethane, and other methyl formate, dimethylformamide, diethylformamide, dimethyl sulfoxide, imidazolium salts, quaternary ammonium salts and other ionic liquids. Further, a mixture thereof may also be used.
[0084] Among these organic solvents, since they are excellent in terms of solubility of the electrolyte, dielectric constant and viscosity, it is particularly preferable to contain one or more non-aqueous solvents selected from the group consisting of carbonate esters.
[0085] In the lithium secondary battery of the present embodiment, in the case of using a polymer electrolyte or a polymer gel electrolyte, examples of those that can be used include: polymers of ethers, esters, siloxanes, acrylonitrile, vinylidene fluoride, hexafluoropropylene, acrylate, methacrylate, styrene, vinyl acetate, vinyl chloride, oxetane, etc. as polymer compounds, or polymers having a copolymer structure thereof, or crosslinked products thereof, etc. The polymer may be one kind or two or more kinds. There is no particular limitation on the polymer structure, and polymers having an ether structure such as polyethylene oxide are particularly preferable.
[0086] In the lithium secondary battery of the present embodiment, the liquid system battery is an electrolyte solution, the gel system battery is a precursor solution obtained by dissolving a polymer in the electrolyte solution, and the solid electrolyte battery is a crosslinked polymer before dissolution of the electrolyte salt accommodated in a battery container.
[0087] The lithium secondary battery of this embodiment can be formed into a cylindrical shape, a coin shape, a square shape, or any other arbitrary shape. Regardless of the shape of the battery, its basic structure is the same, and it can be implemented with design changes according to the purpose. For example, in the case of a cylindrical shape, a negative electrode formed by coating a negative electrode active material on a negative electrode current collector, and a positive electrode formed by coating a positive electrode active material on a positive electrode current collector are wound via a separator, and the resulting wound body is housed in a battery can, a non-aqueous electrolyte is injected, and it is sealed in a state where insulating plates are placed on the top and bottom to obtain. In addition, in the case of being applied to a coin-shaped lithium secondary battery, it is housed in a coin-shaped battery can in a state where a disc-shaped negative electrode, a separator, a disc-shaped positive electrode, and a stainless steel plate are laminated, a non-aqueous electrolyte is injected and sealed.
[0088] Examples
[0089] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0090] <Raw materials used>
[0091] (Polyisocyanate compound)(a)
[0092] · Polyisocyanate compound (a1): Isophorone diisocyanate (molecular weight: 222.3, number of functional groups: 2)
[0093] Polyisocyanate compound (a2): Hydrogenated diphenylmethane diisocyanate (molecular weight: 262, number of functional groups: 2)
[0094] (Polyolefin)(b1)
[0095] · Polyolefin polyol (b1): Krasol LBH-P2000 (manufactured by CRAY VALLEY, polybutadiene polyol) (molecular weight: 2000, number of functional groups: 2)
[0096] (Polycarbonate)(b2)
[0097] · Polycarbonate polyol (b21): DURANOL PCDL T5652 (manufactured by Asahi Kasei, 1,5-pentanediol and 1,6-hexanediol-based polycarbonate polyol) (molecular weight: 2000, number of functional groups: 2)
[0098] · Polycarbonate polyol (b22): ETERNACOLL UH-200 (manufactured by Ube Industries, 1,6-hexanediol-based polycarbonate polyol) (molecular weight: 2000, number of functional groups: 2)
[0099] (Compound having a hydrophilic group and one or more active hydrogen groups)(c)
[0100] · Bis-MPA (Molecular weight: 134.17, Number of functional groups: 2)
[0101] (Chain extender)(d)
[0102] · Amine extender (EDA): Ethylenediamine (Molecular weight: 60.1, Number of functional groups: 2)
[0103] · Amine extender (DETA): Diethylenetriamine (Molecular weight: 103.17, Number of functional groups: 3)
[0104] (Neutralizing salt)
[0105] · Neutralizing salt (TEA): Triethylamine
[0106] · Neutralizing salt (Li): Lithium hydroxide monohydrate (manufactured by NACALAI TESQUE, Inc.)
[0107] <Preparation of polyurethane resin aqueous dispersion>
[0108] (Example 1)
[0109] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 66.1 parts by mass of polyolefin polyol (b1), 10.0 parts by mass of polycarbonate polyol (b21), 4.8 parts by mass of bis-MPA, 18.4 parts by mass of polyisocyanate compound (a1), and 100 parts by mass of methyl ethyl ketone were added. Then, the reaction was carried out at 75 °C for 2 hours to obtain a methyl ethyl ketone solution of a polyurethane prepolymer. The content of free isocyanate groups was 0.85% relative to the non-volatile components of this solution.
[0110] Next, after cooling this solution to 45 °C, 1.5 parts by mass (10% aqueous solution) of lithium hydroxide monohydrate dissolved in water was added thereto for neutralization. Then, while slowly adding 186 parts by mass of water to this solution, an emulsification reaction was carried out using a homogenizer. An aqueous solution obtained by dissolving 0.7 parts by mass of diethylenetriamine (DETA) in 27.00 parts by mass of water was added to the obtained emulsified dispersion, and then the reaction was carried out for 1 hour. Then, by carrying out vacuum distillation of methyl ethyl ketone as a reaction solvent, a polyurethane resin aqueous dispersion having a non-volatile component (solid component) concentration of 35% by mass was obtained. Here, the crosslinking density per 1000 molecular weights of the resin solid component contained in the polyurethane resin aqueous dispersion of Example 1 can be calculated as follows by the above crosslinking density calculation formula.
[0111] 0.7 (parts: amount of DETA) / 103.17 (molecular weight of DETA) / 100 (parts: total amount) × 1000 ≒ 0.07
[0112] (Examples 2 to 6, Comparative Examples 1 to 4)
[0113] Except for changing to the composition shown in Table 1, a polyurethane resin aqueous dispersion was synthesized in the same manner as described in Example 1.
[0114] <Evaluation method>
[0115] The film used in the following evaluations was produced under the following conditions using the above polyurethane resin aqueous dispersion.
[0116] · Film production conditions: 40°C × 15 hours + 80°C × 6 hours + 120°C × 20 minutes
[0117] · Dry film thickness = approximately 300 μm
[0118] The electrolytic solution used in the following evaluations was the following electrolytic solution.
[0119] · Electrolytic solution: Ethylene carbonate / Ethyl methyl carbonate = 1 / 1 (volume ratio) mixed solution
[0120] (Electrolyte resistance)
[0121] A test piece was prepared by cutting out approximately 0.2 g of the film produced as described above. The mass of the test piece before immersion was measured, and then it was immersed in the electrolytic solution at 70°C for 3 days. Then, it was returned to room temperature, and the electrolytic solution on the surface was wiped off. Then, the mass of the test piece after immersion was measured. Then, based on the following formula, the mass increase rate (%) was calculated. The smaller the mass increase rate, the more excellent the electrolyte resistance.
[0122] Mass increase rate (%) = (Mass after immersion - Mass before immersion) / Mass before immersion
[0123] (Ionic conductivity)
[0124] The film produced as described above was cut into a circle with a diameter of 14 mm to prepare a test piece. After measuring the mass and film thickness of the test piece, it was immersed in the electrolytic solution for 12 hours. Then, the immersed test piece was placed in a measurement jig, and then pressure was applied to measure the ionic conductivity.
[0125] <Method for manufacturing the battery used in the experiment>
[0126] (Manufacture of the positive electrode)
[0127] LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3100 parts by mass of O2(NCM), 7.8 parts by mass of acetylene black (manufactured by DENKA Co., Ltd., Li-400) as a conductive agent, 6 parts by mass of polyvinylidene fluoride as a binder, and 61.3 parts by mass of N-methyl-2-pyrrolidone as a dispersion medium were mixed by a planetary mixer to prepare a positive electrode paste with a solid content of 65% by mass. Pure water was used for the preparation of the solid content. The positive electrode paste was coated on an aluminum foil with a thickness of 15 μm using a coater, and then dried at 130 °C and subjected to a rolling process to obtain a positive electrode with a positive electrode active material of 22 mg / cm 2 of the positive electrode.
[0128] (Fabrication of negative electrode)
[0129] 95 parts of a mixture of SiO (average particle size 4.5 μm, specific surface area 5.5 m 2 / g) and graphite (average particle size 18 μm, specific surface area 3.2 m 2 / g) with a content ratio of 20:80 as the negative electrode active material, 2 parts of acetylene black (manufactured by DENKA Co., Ltd.) as a conductive agent, 0.8 part of carboxymethyl cellulose salt (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., WS-C) as a dispersant and binder, 0.2 part (parts by solid content) of fibrous carbon nanotube dispersion (specific surface area: 400 - 500 m 2 / g, fiber diameter 1 - 4 nm) as a binder, and 2 parts (parts by solid content) of the prepared polyurethane resin aqueous dispersion were mixed and then stirred using a homogenizer to prepare a negative electrode paste with a solid content of 48% by mass. Pure water was used for the preparation of the solid content. The negative electrode paste was coated on an electrolytic copper foil with a thickness of 10 μm using a roll coater (manufactured by Sanku Mento Co., Ltd., Titacoater), then dried at 120 °C, and then subjected to a rolling process to obtain a negative electrode with a negative electrode active material of 7 mg / cm 2 of the negative electrode.
[0130] (Fabrication of lithium secondary battery)
[0131] After fabricating the positive electrode and the negative electrode, a polyolefin-based separator was sandwiched between the positive electrode and the negative electrode and laminated, and the electrode tabs were ultrasonically welded to the positive electrode side and the negative electrode side respectively to fabricate a laminated body with electrode tabs. The laminated body with electrode tabs was placed in an aluminum laminated packaging material, and then sealed while leaving an opening for injecting the electrolyte to obtain a battery before electrolyte injection. In the battery before electrolyte injection, the positive electrode area was 18 cm 2 , and the negative electrode area was 19.8 cm 2 . Then, LiPF6 (1.0 mol / L) was dissolved in a solvent obtained by mixing ethylene carbonate and diethyl carbonate at a volume ratio of 30:70, and the resulting electrolyte was injected from the opening, and then the opening was sealed to obtain an evaluation battery.
[0132] <Electrode Adhesion Evaluation>
[0133] (Adhesion Evaluation during Drying)
[0134] Taking the coated surface of the electrode obtained above as the outside, after bending the electrode 180° and returning it, visually judge the degree of shedding of the active material on the coated surface. As the electrode, the negative electrode was used.
[0135] Evaluation Criteria:
[0136] 5 points: 0% or more and less than 25% shedding
[0137] 4 points: 25% or more and less than 50% shedding
[0138] 3 points: 50% or more and less than 75% shedding
[0139] 2 points: 75% or more and less than 100% shedding
[0140] 1 point: 100% shedding
[0141] (Adhesion Evaluation during Wetting)
[0142] Cut the electrode obtained above into a circle with a diameter of 12 mm to make a test piece. After putting the test piece into a 50 mL sample tube, add 5 mL of electrolyte (ethylene carbonate / ethyl methyl carbonate = 1 / 1 (volume ratio) mixed solution), and immerse it for 24 hours. Then, put the sample tube into an ultrasonic cleaner (manufactured by SND Co., 38 kHz) and perform ultrasonic cleaning treatment for 10 minutes. Then, visually judge the degree of shedding of the active material on the coated surface of the electrode. The evaluation criteria are the same as those for the adhesion evaluation during drying.
[0143] (1 kHz ACR)
[0144] After charging the 1 kHz ACR (Alternating Current Resistance) with a CCCV (Constant Current, Constant Voltage) of 0.2C current value for 12 hours, use an impedance analyzer (SP-150 manufactured by biologic company) to measure the resistance value at a frequency of 1 kHz.
[0145] (Discharge Retention Rate)
[0146] The discharge retention rate is measured as follows. First, CC (Constant Current) charging is performed at a current density equivalent to 0.5C up to 4.2V, and then CC discharging is performed at a current density equivalent to 0.5C down to 2.7V. Such a cycle is carried out 300 times at 20°C. Then, the value (%) obtained by dividing the 1C discharge capacity after 300 cycles by the initial 1C discharge capacity is taken as the discharge retention rate.
[0147] The experimental results are shown below.
[0148] [Table 1]
[0149]
[0150] By comparing Examples 1 to 6 and Comparative Examples 1 to 4, it can be seen that by using the polyurethane resin dispersion of the present embodiment, the ionic conductivity, adhesiveness, resistance, and discharge retention rate are balanced and excellent.
[0151] <Impossible / Not practical situation>
[0152] The structure of the polyurethane resin aqueous dispersion of the present embodiment is complex, so it is difficult to represent it by a general formula. Moreover, if the structure is not determined, it is also impossible to easily determine the properties of the substance corresponding to it. That is, the polyurethane resin aqueous dispersion of the present embodiment cannot be directly specified by its structure or properties.
[0153] Industrial applicability
[0154] The polyurethane resin aqueous dispersion of the present embodiment can be used as a binder for electrodes of lithium secondary batteries, and the electrodes using this binder are used in the manufacture of various lithium secondary batteries. The obtained lithium secondary batteries can be used in various portable devices such as mobile phones, laptop computers, portable information terminals (PDAs), video cameras, digital cameras, etc., as well as medium-sized or large-sized lithium secondary batteries mounted on electric bicycles, electric vehicles, etc.
[0155] The present invention is not limited to the above embodiments and can be implemented in various structures without exceeding its spirit. For example, in order to solve part or all of the above problems or to achieve part or all of the above effects, the technical features in the embodiments and examples corresponding to the technical features in each mode described in the invention content column can be appropriately replaced and combined. In addition, if the technical features are not described as essential content in this specification, they can be appropriately deleted.
Claims
1. A polyurethane resin aqueous dispersion for a binder, which is a polyurethane resin aqueous dispersion for a binder used in a lithium secondary battery, and is characterized in that it is a polyurethane resin aqueous dispersion obtained by dispersing a polyurethane resin obtained by reacting a polyisocyanate compound (a), a compound (b) having two or more active hydrogen groups, a compound (c) having a hydrophilic group and one or more active hydrogen groups, and a chain extender (d) in water. The compound (b) contains: a polyolefin (b1) having two or more active hydrogen groups, and a polycarbonate (b2) having two or more active hydrogen groups and having 6 or less consecutive carbon atoms, and relative to 100 parts by mass of the total blending amount of the polyolefin (b1) and the polycarbonate (b2), the polycarbonate (b2) is 5 parts by mass or more and 95 parts by mass or less, and the crosslinking density per 1000 molecular weights of the resin solid content contained in the polyurethane resin aqueous dispersion is 0.02 mol / kg or more and 0.28 mol / kg or less.
2. The polyurethane resin aqueous dispersion for a binder according to claim 1, characterized in that relative to 100 parts by mass of the total blending amount of the polyolefin (b1) and the polycarbonate (b2), the polycarbonate (b2) is 40 parts by mass or more and 80 parts by mass or less.
3. The polyurethane resin aqueous dispersion for a binder according to claim 1, characterized in that the polyisocyanate compound (a) contains at least one of an aromatic polyisocyanate and an alicyclic polyisocyanate.
4. The polyurethane resin aqueous dispersion for a binder according to any one of claims 1 to 3, characterized in that the polyolefin (b1) contains a polyolefin having two or more hydroxyl groups.
5. The polyurethane resin aqueous dispersion for a binder according to any one of claims 1 to 3, characterized in that the polycarbonate (b2) contains a polycarbonate having two or more hydroxyl groups.
6. The polyurethane resin aqueous dispersion for a binder according to any one of claims 1 to 3, characterized in that the compound (c) contains a compound having an active hydrogen group and a carboxyl group.
7. The polyurethane resin aqueous dispersion for a binder according to any one of claims 1 to 3, characterized in that the chain extender (d) contains a triamine.
8. The polyurethane resin aqueous dispersion for a binder according to any one of claims 1 to 3, characterized in that relative to 100 parts by mass of the total blending amount of the polyisocyanate compound (a), the compound (b), the compound (c) and the chain extender (d), the chain extender (d) is 0.2 parts by mass or more and 1 part by mass or less.
9. An electrode binder, characterized in that the electrode binder contains the polyurethane resin aqueous dispersion for a binder according to any one of claims 1 to 8.
10. A lithium secondary battery, characterized in that the lithium secondary battery includes an electrode using the electrode binder according to claim 9.
Citation Information
Patent Citations
Nonaqueous solvent secondary battery
JP1993021068A
Nickel-hydrogen battery anode and manufacture thereof
JP1999007948A
Manufacturing method of negative electrode for nonaqueous electrolytic solution secondary battery
JP2001210318A
Binder for electrode in lithium secondary cell, electrode manufactured using said binder, and lithium secondary cell in which said electrode is used
CN105378988A
Cited By
A low-polarity crosslinking type waterborne polyurethane binder suitable for silicon-carbon negative electrodes and a preparation method thereof
CN122503073A